Proceeding of A3 Foresight Program Seminar on Critical Physics Issues Specific to Steady State Sustainment of High-Performance Plasmas November 22-25, 2016, Jeju, Korea - Yeong-Kok, Oh, editor; Shigeru MORITA, editor; Liqun, Hu, editor; National Institute for Fusion Science (Toki, Japan : National Institute for Fusion Science, 2018)
PSZJBL